2021
DOI: 10.3389/fnut.2021.638259
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior, Health-Related Quality of Life, and Mental Health Among Canadian Children: A Population-Based Cohort Study

Abstract: Objective: Studies that have reported the associations of diet quality, physical activity (PA), sedentary behavior (SB), and health-related quality of life (HRQoL) with mental health among children and adolescents are predominantly cross-sectional in design. Very few studies have examined the longitudinal relationship of mental health with health behavior and HRQoL among children. This study aimed to investigate the associations of diet quality, PA, SB, and HRQoL among children with mental health disorders thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…A few studies showed that compared to TD children, children with ASD aged 4–10 years have less frequent milk intake ( 24 , 25 ). Two studies indicated that meeting recommendations for milk and alternative in childhood was associated with fewer health care encounters for mental illnesses, such as depressive episodes, mood disorder, general anxiety disorder, attention-deficit/hyperactivity disorder (ADHD), and so on ( 26 , 27 ). Therefore, it's reasonable to speculate that milk intake was negatively associated with emotional and behavioral problems, and there were interactive effects between SSBs and milk intake on emotional and behavioral problems in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies showed that compared to TD children, children with ASD aged 4–10 years have less frequent milk intake ( 24 , 25 ). Two studies indicated that meeting recommendations for milk and alternative in childhood was associated with fewer health care encounters for mental illnesses, such as depressive episodes, mood disorder, general anxiety disorder, attention-deficit/hyperactivity disorder (ADHD), and so on ( 26 , 27 ). Therefore, it's reasonable to speculate that milk intake was negatively associated with emotional and behavioral problems, and there were interactive effects between SSBs and milk intake on emotional and behavioral problems in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal studies showed a long-term relationship between PA and psychological constructs, but the results are inconsistent (Wu et al, 2018 , 2021 ; Doré et al, 2019 , 2020 ; Kleppang et al, 2019 ; Loewen et al, 2019 ; Gómez-Baya et al, 2020 ; Hamer et al, 2020 ; Isaksson et al, 2020 ; Kandola et al, 2020 ; van Woudenberg et al, 2020 ; Bowe et al, 2021 ). To illustrate some results, Nigg et al concluded that PA may not be a preventive component for mental health problems, but mental health problems can be a risk factor for lower activity at preadolescent ages (Nigg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies provide information that PA may be a promising factor within a treatment program for ADHD symptoms (Halperin et al, 2014 ; Khalife et al, 2014 ; Cerrillo-Urbina et al, 2015 ; Rommel et al, 2015 ; Ng et al, 2017 ; Ahn et al, 2018 ; Wu et al, 2018 , 2021 ; Biddle et al, 2019 ; Neudecker et al, 2019 ; Miklós et al, 2020 ; Vysniauske et al, 2020 ; Mercurio et al, 2021 ). Biddle et al concluded from systematic reviews and meta-analyses that PA leads to better cognitive results and academic achievement (Biddle et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents’ mental health issues are becoming a significant global public health concern, significantly burdening the existing healthcare system [ 1 , 2 ]. Mental illness negatively affects adolescents, their parents, and surrounding families, especially regarding health-related quality of life (HrQoL) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although HrQoL is commonly used to influence health and welfare policy, it is understudied in community settings, especially among adolescents experiencing mental health issues at an increasing rate [ 17 , 18 ]. Therefore, a better understanding of the link between mental health issues and health-related quality of life in adolescents is a top priority, with significant implications for improving HrQoL in the face of mental health issues [ 2 ].…”
Section: Introductionmentioning
confidence: 99%